6+4(3-k)=3(-2k+9)

Simple and best practice solution for 6+4(3-k)=3(-2k+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4(3-k)=3(-2k+9) equation:



6+4(3-k)=3(-2k+9)
We move all terms to the left:
6+4(3-k)-(3(-2k+9))=0
We add all the numbers together, and all the variables
4(-1k+3)-(3(-2k+9))+6=0
We multiply parentheses
-4k-(3(-2k+9))+12+6=0
We calculate terms in parentheses: -(3(-2k+9)), so:
3(-2k+9)
We multiply parentheses
-6k+27
Back to the equation:
-(-6k+27)
We add all the numbers together, and all the variables
-4k-(-6k+27)+18=0
We get rid of parentheses
-4k+6k-27+18=0
We add all the numbers together, and all the variables
2k-9=0
We move all terms containing k to the left, all other terms to the right
2k=9
k=9/2
k=4+1/2

See similar equations:

| 2x+1=1/3+5 | | 6x+12=8N | | 4(2x+2)=56 | | 5f+6=31 | | −5x=−18 | | 2+34(x-5)=5 | | 4/7(21/8x+0.5)=-2(1/7-5/28) | | 1/4=4x-3 | | 5(y+2/5=-3 | | 4^x=85 | | k^2+8k-12=48 | | 6-4x=6x=8x+4 | | 2t^2-16t+40=20 | | 50=-5(v-9) | | 54=3(r-70) | | 50=-5(v–9) | | 54=4(r-70) | | 13-u/2=14 | | x*3/5=2/5 | | 13–u2=14 | | (3x+15)+(2x+35)=180 | | (2^n)-1=10 | | x+3/5=2/5 | | 5x+2+6x+3=50 | | 2^n - 1=10 | | -70=7(s-12) | | 5(4)^2x=13 | | 2^n- 1=10 | | X+y/2=280 | | 0.045x=9000 | | 8yy=5 | | 45x+x=4x |

Equations solver categories